Information sharing in military operations - Goldenberg, Irina; Soeters, Joseph; Dean, Waylon H. (Advanced sciences and technologies for security applications, 2017)
This volume explores the interpersonal, organizational, and technological enablers and barriers to information and intelligence sharing in multinational and multiagency military, humanitarian, and counterterrorism operations.